Influence of point defects and impurities on the dynamical stability of δ-plutonium. (17th May 2017) - Dorado, B; Bieder, J; Torrent, M
Abstract: We use first-principles calculations to provide direct evidence of the effect of aluminum, gallium, iron and uranium on the dynamical stability of δ -plutonium. We first show that the δ phase is dynamically unstable at low temperature, as seen in experiments, and that this stability directly depends on the plutonium 5 f orbital occupancies. Then, we demonstrate that both aluminum and gallium stabilize the δ phase, contrary to iron. As for uranium, which is created during self-irradiation and whose effect on plutonium has yet to be understood, we show that it leaves a few unstable vibrational modes and that higher concentrations lead to an almost complete stabilization. Finally, we provide an attempt at a consistent analysis of the experimental Pu–Ga phonon density of states. We show that the presence of gallium can reproduce only partially the experimental measurements, and we investigate how point defects, such as interstitials and vacancies, affect the calculated phonon density of states.